Caloric stress index quantification for dairy cows in Anguil, La Pampa (Argentina) (Semiárida, 2020)
The present study is an environmental characterization of the area near Anguil INTA experimental station (La Pampa, Argentina) using the temperature and humidity index, which refers to animal comfort, specifically applicable to lactating dairy cows. The objective of this work was to detemined whether these animals suffer heat stress and its effect on milk production. The data set includes 10-year hourly values for the November to March period. The results indicate that some heat stress occurs during summer, although limiting values are not reached and stress does not last for long periods.
Keywords: Anguil; THI; temperature; humidity; stress; dairy production